DEIXIS IN RADITYA DIKA’S UTTERANCES IN STAND-UP COMEDY SHOW - Harna Malau; Lince Sihombing (LINGUISTICA, 2013)
ABSTRACT This study deals with how often Raditya Dika produces types of deixis in stand-up comedy show. This research was based on descriptive design by applying qualitative method and converting the data numerically. The data of this study  were the three selected videos of Raditya dika downloaded from youtube. There were 709 sentences produced after transcribing those videos into written language. The findings of this study show that those five types of deixis were found in Raditya Dika’s utterances, they are: person (68.94%), spatial (5.24%), temporal (5.83%), discourse (8.60%) and social (11.37%). The most dominant type of deixis found is person deixis with “gue” or “I” as the dominant deictic word. Person deixis is dominantly used because the comics in stand-up comedy conduct first point of view that make the use of personal pronoun more often than others. Keywords: Deixis, Utterances, Stand-up comedy.